'King Bottomless Empty Purse': Taxes, Avarice and Pastoral Care in the Swedish Reign of Christian I (1457–64). Issue 2 (15th March 2021) - Tjällén, Biörn
ABSTRACT: Taxes were at the heart of late medieval political discourse because tax extraction was a tangible and sore point of interaction between subjects and their rulers. At no point in Swedish history was this more obvious than in the reign of Christian I (1457–64), and this article takes his reign as a moment to explore the parameters of the fiscal discourse where taxes were refuted or accepted. The first part examines the fiscal norms of law and custom, which were expressed in the pamphlets and chronicles that testify to Sweden's burgeoning public sphere. The second part, however, focuses on the moralizing tenor of these narratives, where the tax abuse by Christian and other rulers is considered not only a crime but also a sin, and in particular avarice. The third part of the inquiry maps this moralizing tenor to its source in the penitential literature that guided the pastoral care of rulers and subjects alike. Taxes, this article contends, were not only talked about in the idioms of law and custom but also in the language of moral theology and pastoral care. Penance and politics were entwined in a way that shaped how taxes were talked about in public life.